SARA: Videojuego Para el Aprendizaje Agrícola Soportado en Dinámica de Sistemas (DS) - Prada, Urbano Eliécer Gómez (KnE Engineering, 2018)
SARA is a videogame for the learning of agricultural production systems, in which the player simulates the decisions that would take in a greenhouse and concentrate them in a web portal for its subsequent follow-up, traceability and contrast of results in a way that favors the learning process. The game rules are supported in a simulation model elaborated with Systems Dynamics (SD). Keywords: Serious Videogame, Learning, Agriculture, Systems Dynamics, Web Information System, Knowledge Representation